Ethanol Sclerotherapy versus Laparoscopic Surgery in Management of Ovarian Endometrioma; a Randomized Clinical Trial - Ghasemi Tehrani, Hatav; Tavakoli, Raheleh; Hashemi, Maryam; Haghighat, Somayeh (Archives of Academic Emergency Medicine, 2022)
Introduction: A variety of therapeutic modalities are available in management of ovarian endometrioma. This study aimed to compare the effects of ethanol sclerotherapy and laparoscopic surgery on disease recurrence and ovarian factors of these patients. Methods: 70 women with ovarian endometrioma and chronic pelvic pain were randomly divided into two groups. The first group underwent sclerotherapy with a puncture needle (cook) and the second group underwent laparoscopic surgery. Both groups were followed up every three months to investigate the recurrence rate. In this regard, ultrasonography was performed 3 months and 12 months after treatment, and serum anti-Müllerian hormone (AMH) levels were also reassessed 12 weeks after the intervention. Results: 70 women with the mean age of 31.46 ± 4.71 years, and the mean body mass index (BMI) of 23.12 ± 1.01 were studied. The two groups were similar regarding age (p = 0.770), BMI (p = 0.371), history of gastrointestinal signs (p = 0.794), history of urinary diseases (p = 0.324), dysmenorrhea (p = 0.403), pelvic pain (p = 0.454), dyspareunia (p = 0.448), location of cyst (p = 0.448), and diameter of cyst (p = 0.250). In the laparoscopic group, a significant decrease in anti-Müllerian hormone (AMH) levels was observed after 12 weeks (p < 0.0001), while in the sclerotherapy group, no significant changes were found between pre-and post-operative AMH levels (p = 0.120). Cyst size decreased significantly in both groups three months (p < 0.001) and twelve months (p < 0.0001) after treatment. In the third month, 8 patients in the sclerotherapy group and 13 patients in the laparoscopic group had recurrences, and in the twelfth month, 17 patients in the sclerotherapy group and 15 patients in the laparoscopic group had recurrence of symptoms (p > 0.05). Conclusions: Although AMH level and mean cyst diameter were significantly lower one year after laparoscopy, recurrence rate of ovarian endometrioma was similar between ethanol sclerotherapy and laparoscopy methods.